Language Acquisition: The Interaction between Innate Capacity and Language Input - Nurdiana Nurdiana (Journal of English Language and Culture, 2017)
Numerous studies on how language is acquired have been conducted for years and myriad theories on language acquisition have put attempts to explain how human beings acquire language, e.g. language learning through imitation, reinforcement, association, and the innateness hypothesis. This paper shall describe the language acquisition process through the innateness hypothesis. It argues that language is acquired through an interaction between innate capacity—an innate ability to produce words and utterances—and language input, the language acquired from the human surroundings. Keywords: language acquisition, language input, innate capacity